Viscoelastic effects on the double-diffusive oscillatory flow in a fluid-saturated porous layer - Raghunatha, K. R.; Vinod, Y.; İnç, Mustafa; Yildirim, Elif Nuray (World Scientific Publ Co Pte Ltd, 2023)
The viscoelastic effects on the double diffusive oscillatory flow in a fluid-saturated porous layer are investigated. A modified Darcy-Oldroyd-B model is used to characterize the non-Newtonian fluid behavior flow in a porous layer. Analytic solutions of the dimensionless governing equations of fluid flow are obtained and the effects of the flow parameters on temperature, concentration, velocity profiles, skin friction and rate of heat transfer are discussed and shown graphically. It is interesting to note that skin friction increases on both channel plates as injection increases on the heated plate. Increase in the strain retardation parameter is to decrease the fluid velocity, while an opposite trend is noticed with increasing stress relaxation parameter. The study reiterates that the consideration of viscoelastic fluid is very important in proper considerate of oscillatory flow in double diffusive fluid systems.
Keywords: Double-diffusive convection; viscoelastic fluids; oscillatory flow; porous layer